Microstructure and phase evolution of micronized ceramic colorants from a pilot plant for inks production. Issue 1 (1st January 2023) - Ardit, Matteo; Molinari, Chiara; Verucchi, Daniele; Tintorri, Alice; Migliori, Michela; Toschi, Tanya; Conte, Sonia; Zanelli, Chiara; Cruciani, Giuseppe; Dondi, Michele
Abstract: The advent of inkjet printing as digital decoration of ceramic materials has irreversibly modified the industrial decoration technology, imposing companies to change the colorant production process. The inkjet application requires micronized particles in the ultrafine particle size range (smaller than 1 μm). Particles size reduction of ceramic colorants is performed by a high-energy comminution process in wet-operated bead mills, affecting colorants properties. Since a deep knowledge of milling-induced microstructural changes is still lacking, the micronization effects on a set of five industrial ceramic colorants are thoughtfully investigated in this work by simulating the industrial process at a pilot plant. Particle size distribution and energy consumption are monitored during the comminution process. The compositional (including crystallite size and microstrain analysis of the main phases) and morphological variation of four ceramic pigments (yellow zircon, brown spinel, pink malayaite, and green eskolaite) and one dye (blue olivine) is investigated by XRPD (Rietveld method) and SEM analyses. The analytical approach combined with a physical/semiempirical modelling of the colorants elastic features versus the energy demand for particle reduction has yielded details on the nature of the micronization-induced microstructural changes in ceramic colorants. Specifically, the comminution efficiency as well as the crystalline phase stability are related to the intrinsic properties of each colorant. Brittle breakage rather than plastic deformation on comminution are also system dependent. When an euhedral to subhedral crystal habit is maintained a brittle fracture is preserved throughout the comminution progress, while the formation of flake-like particles and particle agglomeration are strong evidences of plastic deformation. The last evidence deals with the material elastic features. Materials with high bulk modulus convert the grinding energy to lattice defects that lead to particle breakage by brittle fractures, while materials with lower bulk modulus convert/dissipate part of the supplied energy in plastic deformations, drastically decreasing the comminution process efficiency.